Utility of cardiac biomarkers (NT-proBNP and Hs-troponin-T) in predicting mortality, cardiovascular and renal outcomes in patients with chronic kidney disease - Senthil Kandaswamy (Clinical Medicine)
Introduction: Chronic kidney disease (CKD) is strongly linked to cardiovascular disease (CVD), partly because of shared common traditional risk factors and, therefore, it may be intuitive to use CVD biomarkers in CKD risk prediction and vice versa. Cardiac biomarkers, N-terminal pro-B-type natriuretic peptide (NT-proBNP) and high-sensitivity cardiac troponin-T (Hs-cTnT), are good prognostic indicators of long-term clinical cardiovascular outcomes in patients with CKD.1–3 However, the clinical utility of combined biomarkers in predicting death and cardiorenal outcomes in patients with CKD remains unclear. This study examined the prognostic accuracy and incremental value of NT-proBNP and Hs-cTnT for all-cause mortality, major adverse cardiovascular events (MACE) and end-stage kidney disease (ESKD) in non-dialysis-dependent (NDD)-CKD patients. Materials and Methods: Data from 1,946 individuals with NDD-CKD prospectively included in the Salford Kidney Study4 were used to investigate the associations between NT-proBNP and Hs-cTnT with study endpoints. Hazards ratio (HR) or subhazards ratio (sHR) and 95% confidence intervals (95% CI) were estimated using multivariate Cox-regression and competing risk models. Multivariate models were adjusted for age, gender, smoking status, blood pressure, baseline comorbidity (diabetes, heart failure, ischaemic heart disease or myocardial infarction, stroke, peripheral vascular disease, atrial fibrillation for all-cause mortality, and ESKD and diabetes only for MACE), baseline medication use (ACE and/or ARB and/or statin) and mutually for NT-proBNP and Hs-cTnT. The discriminatory power of NT-proBNP and Hs-cTnT along with kidney biomarkers (estimated glomerular filtration rate (eGFR) and urine albumin–creatinine ratio (uACR)) and Framingham Risk score (FRS) were calculated using Harrell’s C-index. Data were analysed using STATA IC/16.0. Results and Discussion: During a median follow-up of 71.5 months, 931 (47.8%) deaths, 553 (28.4%) MACE and 554 (28.5%) ESKD events occurred. Higher quartiles of NT-proBNP and Hs-cTnT showed an increasing risk trend with mortality, MACE and ESKD (Table 1). Our findings are consistent with previous studies that showed that higher levels of cardiac biomarkers are associated with greater risk of mortality, MACE and ESKD.2,5,6 In patients with CKD stage 3–5, higher NT-proBNP and Hs-cTnT quartiles were associated with significant risk for mortality and MACE, while eGFR and uACR were associated with a two-to-fourfold increased risk of ESKD or renal replacement therapy, as shown previously.7,8 Combining NT-proBNP, Hs-cTnT and FRS yielded the highest prognostic accuracy for all-cause mortality and MACE (respective C-statistics: 0.713 and 0.697) while combining NT-proBNP and Hs-cTnT with eGFR and uACR performed best at predicting ESKD (C-statistics:0.821; 95% CI: 0.786–0.826), which aligns with findings from the Chronic Renal Insufficient Cohort (CRIC).9 Conclusion: In NDD-CKD patients, NT-proBNP and Hs-cTnT are robust predictors of all-cause mortality, MACE and ESKD, independently of kidney biomarkers. Combining NT-proBNP and Hs-cTnT with eGFR and uACR outperformed risk prediction for ESKD compared with eGFR and uACR used alone or in combination.